2018
DOI: 10.1037/cbs0000094
|View full text |Cite
|
Sign up to set email alerts
|

Énaction et intervention en psychologie du sport chez les sportifs élites et en formation.

Abstract: Cet article présente l'apport potentiel des approches énactives en psychologie du sport et, plus particulièrement, de l'accompagnement psychologique des sportifs d'élite et en formation. Les hypothèses théoriques de l'énaction sont d'abord définies et illustrées par des travaux de recherche menés en psychologie du sport. Puis, les principes méthodologiques et pratiques d'une intervention énactive auprès de sportifs d'élite sont présentés. Trois interventions énactives spécifiques sont ainsi cernées et illustré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 60 publications
1
24
0
1
Order By: Relevance
“…A way to efficiently combine the emergence of bad physical sensations and the need for adaptation to environmental conditions would be – when possible – resting when the meteorological conditions are poor. Last, the enactive interviews could be used for intervention to (1) improve athletes’ follow-up for sports psychologists, (2) invite reflexive practice on one’s own activity to develop a better understanding of performance by reliving one’s past experience (Hauw, 2009, 2018), and (3) investigate the suffering episodes and critical situations in greater detail by reducing the granularity of analysis using micro-phenomenological interviews (e.g., Depraz et al, 2017). In doing so, we may expect that runners are able to connect these typical gestalts to their own personal experiences and stories as trail runners in order to sustain an autonomous, responsible, and self-regulated approach to their sport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A way to efficiently combine the emergence of bad physical sensations and the need for adaptation to environmental conditions would be – when possible – resting when the meteorological conditions are poor. Last, the enactive interviews could be used for intervention to (1) improve athletes’ follow-up for sports psychologists, (2) invite reflexive practice on one’s own activity to develop a better understanding of performance by reliving one’s past experience (Hauw, 2009, 2018), and (3) investigate the suffering episodes and critical situations in greater detail by reducing the granularity of analysis using micro-phenomenological interviews (e.g., Depraz et al, 2017). In doing so, we may expect that runners are able to connect these typical gestalts to their own personal experiences and stories as trail runners in order to sustain an autonomous, responsible, and self-regulated approach to their sport.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, within the sports psychology literature, the course-of-action framework has already been used to gain insight into performance in many sports like trampoline and acrobatics (Hauw and Durand, 2004, 2008), skydiving (Mohamed et al, 2015), table tennis (Sève et al, 2005), orienteering (Mottet et al, 2016), rowing (Sève et al, 2013), soccer (Villemain and Hauw, 2014; Gesbert et al, 2017), and trail running (Antonini Philippe et al, 2016; Hauw et al, 2017; Rochat et al, 2017). All these studies analyzed embedded activity through activity analysis and were able to provide practical recommendations for training, education, and competition (e.g., Hauw, 2017, 2018). Therefore, for research into athletes’ embedded activity, the course-of-action framework provides the methodological tools to identify the temporal and meaningful structures of experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that psychological preparation strategies can be successfully utilized to combat negative emotional states often experienced by athletes as anxiety, and to prolong high levels of adherence and performance throughout the sporting season [2]. A better understanding of the predictors of anxiety, motivational climate, and mental health enables efficacious strategies to be designed for various sport modalities [2][3][4]. The influence of the specific characteristics of various types of sports (including their internal dynamics, ways of association, or forms of contact between rivals and peers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to bring out the significant elements of the experience when practicing or learning a sports activity. There is an important body of literature in which researchers often combine biomechanical data with that obtained from interviews with athletes and learners in PE and sports (Hauw and Durand, 2007;Bourbousson et al, 2012;Sève et al, 2013;Evin et al, 2014;Terré et al, 2016;Rochat et al, 2017Rochat et al, , 2019Hauw, 2018;Récopé et al, 2019). Although each study is unique, the general method has been to reconstruct the course of action (Theureau, 2010) to "capture" the performer's experience by verbalizing it in self-confrontation interviews.…”
Section: The Subjective Universe Of Learners and Experiencementioning
confidence: 99%